IMPLEMENTASI PENDIDIKAN IBADAH DI TAMAN KANAK-KANAK ABA MUTTAHIDAH LUWUK - Kusno Setiadi; Dhia Syafiqa; Sindi Sulfina; Wulandari; Khaerul Akbar (Awladuna: Jurnal Pendidikan Islam Anak Usia Dini, 2024)
A person's personal character is reflected in the way they live their religious teachings. Character is developed through formal education. The role of schools as educational institutions is obliged to provide character education for children. More specifically, children's character is formed from religion, namely worship education. So schools from elementary level such as kindergarten need to implement worship education. The aim of this research is to describe the implementation of worship education at the ABA Muttahidah Luwuk Kindergarten. The research approach used is descriptive qualitative. The research results show that worship education at the ABA Muttahidah Luwuk Kindergarten This aims to ensure that students can worship correctly according to Islamic teachings and be devoted to Allah SWT. Worship education can be done by learning to read prayers, pray and recite the Koran. There are obstacles in implementing worship education, AUD teachers as mentors, role models, facilitators and motivators play a very important role in optimizing Worship Education at the ABA Muttahidah Luwuk Kindergarten. From these findings, it is hoped that schools or kindergartens, school principals, AUD teachers will always innovate in Worship Education through varied methods, media and learning resources.